Pelleting of a Total Mixed Ration Affects Growth Performance of Fattening Lambs - Li, Bo; Sun, Xuezhao; Huo, Qin; Zhang, Guiguo; Wu, Tingting; You, Peihua; He, Yuhua; Tian, Wannian; Li, Rongquan; Li, Changsheng; Li, Jianping; Wang, Chunqing; et al. (Frontiers in Veterinary Science, 2021)
Feeding pelleted total mixed rations (TMR) instead of traditional loose concentrate plus forage to fattening lambs is an emerging practice. This study aimed to determine the effects of feeding pelleted TMR to fattening lambs on feed intake behaviour, growth performance, feed digestion, rumen fermentation characteristics, rumen microbial community, serum parameters, slaughter performance, meat quality, and the economic outcome. Two physical forms (pelleted versus un-pelleted) of TMR composed of the same ingredients with the same particle sizes were compared in three animal experiments. Feed intake and average daily gain were higher when the TMR was pelleted, but apparent total tract digestibility of nutrients (organic matter, crude protein, neutral detergent fibre, acid detergent fibre, and ether extract) and serum parameters were not affected and apparent total tract dry matter digestibility was slightly lower. Feeding pelleted TMR increased total short-chain fatty acid concentration and decreased rumen pH. Rumen microbial community was not affected by the physical form of the TMR at phylum level but changed slightly at genus level. Liveweight at slaughter and hot carcass weight were higher for lambs fed the pelleted compared to the un-pelleted TMR, while dressing percentage and meat quality were not affected. In conclusion, feeding pelleted TMR improves growth performance of fattening lambs mainly due to an increase in feed intake. Feeding pelleted TMR is a feasible strategy for intensive lamb fattening operations.